THE EFFECT OF INFORMATION TRANSFORMATION AND PROMOTION ON CUSTOMER DECISIONS AT PT FIFGROUP MEDAN II BRANCH - Eva Margareth Sarah; Mega Ulva Sari Sihombing; Niscaya Hia; Denata Br Tarigan (Universitas Dharmawangsa Medan, 2026)
The purpose of this study is to determine how promotions and information transformation influence customer choices for financing services at PT FIF Group Medan II Branch. Information transformation through social media, websites, and applications is crucial due to the evolution of consumer behavior that increasingly relies on digital channels for information seeking. This research methodology is a quantitative associative strategy with accidental sampling. Fifgroup clients are the research population, and the Slovin method is used to calculate a sample size of 78 respondents. Multiple linear regression is used to analyze the data and determine how each independent variable affects the other variables. The research findings indicate that although the promotion variable (X2) has a positive influence on the consumer decision variable (Y), the information transformation variable (X1) also has a positive influence on that variable. From the combination of each variable, it can be concluded that information transformation and promotions have a positive influence on consumer decisions because the F-value = 42.683 is greater than the F-value = 3.12 and the significance value = 0.000 is smaller than the α value = 0.05. SPSS V26 software is used to process data statistically.